Experimental study on bentonite stabilisation using construction waste and slag - Hasan, Umair (Curtin University, 2015)
Feasibility of stabilising bentonite with greener additives, construction waste and slag, was investigated. Addition of both additives improved unconfined compressive and direct shear strengths, optimum additives as 20% of construction waste and 5% of slag under all curing conditions. Effect was more pronounced with successive curing periods, showing highest value for 28 days curing. Presence of slag and bentonite grains in vesicles of construction waste particles was observed through SEM, EDS and XRD results.